Functional beauty - Parsons, Glenn; Carlson, Allen (Oxford : Oxford University Press, 2008)
The authors examine the relationship between function and aesthetic value. They develop the concept of functional beauty drawing on work in the philosophy of science as well as aesthetics, and show its importance in diverse kinds of aesthetic appreciation - of buildings, nature, everyday objects and events.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Aesthetics